The effectiveness of socrative and kahoot to teach grammar to students with different interest - Maesaroh, Maesaroh; Faridi, Abdurrachman; Anggani Linggar Bharati, Dwi (English Education Journal, 2020)
This study aimed at examining the effectiveness of socrative and kahootto teach grammar to students with different interest. The objectives of the study are, to analyze high and low interest students’ score of grammar in order to explain the effectiveness of socrative, to analyze high and low interest students’ score of grammar in order to explain the effectiveness of kahoot, to analyze the significant difference between the students with high interest after taught by using Socrative and Kahoot to teach grammar, to analyze the significant difference between the students with low interest after taught by using Socrative and Kahoot to teach grammar, to analyze how the interaction is among teaching, students’ interest and grammar. It was an experimental research with 2x2 factorial design. I used questionnaire, observation and test. The data from questionnaire and grammar test is analyzed quantitatively using T-test and ANOVA.The results of this research showed that socrative to students with high and low interest (79.17 and 57.50) and kahoot to students with high and low interest (85.50 and 62.86) are effective. Mean score of kahoot multimedia was higher than socrative in teaching grammar. There was no significant interaction among multimedia, interest and students’ grammar achievement..